Pengembangan Media Pembelajaran Bangun Ruang Menggunakan Adobe Animate di Sekolah Dasar - Sasongko, Timbul (Jurnal Didaktika Pendidikan Dasar, 2025)
This research is aimed to develop three-dimensional using Adobe Animate and then evaluate it on Class VI Elementary School students from the population. The specific objectives of this research are to reveal: relevance of the Adobe Animate program for spatial learning, students’ opinions regarding the learning media used, observers’ opinions regarding computer-assisted spatial learning products. This research is R&D (Reasearch and Development). The development procedure are: 1) Research and Information Collection, 2) Planning, 3) Develop Preliminary form of Product, 4) Priminary Field Testing, 5) Main Product Revision, 6) Main Field Testing, 7) Operational Product Revision, 8) Operational Field Testing, 9) Final Product Revision, 10) Dissemination and Implementation. The subjects research of 21 respondents of: 1 Teacher and 6 Students small group, 1 Teacher and 12 Students large group, 1 Teacher and 18 Students field trial. Data collection uses questionnaires and three-dimensional Mathematics tests (Pre-test and Post-test). Evaluation materials aspects and media. Criticism and suggestions to improve program. The results of research from learning and media aspects, the Adobe Animate program three-dimensional stated to interesting, learning motivation (rated A/very high) by respondents, the average score of the Post-test compared to the Pre-test by 5,6%.